Dividend-Timing Strategy and Market Performance: Evidence From Indonesian Listed Companies - Nurfitri Desliniati; Kesuma, Wendy; Safitri, Dwi Islamiyati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Stock price fluctuations around dividend distribution dates create opportunities for short-term trading strategies known as the dividend-timing strategy. This study analyzes the performance of the dividend-timing model among companies listed on the Indonesia Stock Exchange (IDX) during 2018–2025 by examining returns and risks across various time horizons and comparing them with the Indonesia Composite Index (IHSG). The results show that the dividend-timing model consistently generates positive returns across all horizons, with the highest return observed in Horizon 1—buying three days before the cum-dividend date and selling at the opening price on the ex-dividend date. Horizon 7 exhibits the lowest level of risk, indicated by the smallest Price Drop Ratio (PDR). Compared with the IHSG, this model provides higher returns and lower risk. These findings indicate that dividend-based strategies can serve as an effective short-term investment approach, offering attractive returns with controlled risk.